A review of nemorosone: Chemistry and biological properties. (June 2023) - Cuesta-Rubio, Osmany; Monzote, Lianet; Fernández-Acosta, Roberto; Pardo-Andreu, Gilberto Lázaro; Rastrelli, Luca
Abstract: Nemorosone is a bicyclic polyprenylated acylphloroglucinol derivative originally isolated from Clusia spp. and it can be obtained through chemical synthesis employing different synthetic strategies. Since its discovery, it has attracted great attention both from a biological and chemical viewpoint. In the present article, we attempted to review various chemical and biological topics around nemorosone, with an emphasis on its antiproliferative activities. For this purpose, relevant data was collected from different scientific databases including Google Scholar, PubMed, Scopus and ISI Web of Knowledge. This natural compound has shown activity against several types of malignancies such as leukemia, human colorectal, pancreatic, and breast cancer because it modulates multiple molecular pathways. Nemorosone has both cytostatic and cytotoxic activity and it also seems to induce apoptosis and ferroptosis. Additionally, it has antimicrobial capabilities against Gram-positive bacteria and parasites belonging to genus Leishmania . Its promising antiproliferative pre-clinical effects deserve further attention for anticancer and anti-parasitic drug development and translation to the clinic. Graphical abstract: Image 1 Highlights: Nemorosone is a bicyclic polyprenylated acylphloroglucinol with antiproliferative effect. Nemorosone is the main component of Clusiaceae floral and tropical propolis. Nemorosone is a leading compound with various biological activities. Chemistry and biological properties of nemorosone are updated and analyzed in this review.